Visual Interventions: The Power of the Pen for Effective Communication - Gross, Stefan (Journal of Education and Research, 2015)
Pictures, words, and patterns are the major tools of visual facilitation. Ever since, these powerful tools have been used live in discussions to support brainstorming, decision-making or teaching and learning processes. However, their utilization as a powerful instrument today is lacking of a theory that helps to understand conditions, possibilities and effects of visual interventions for effective communication. This article is a first step towards this direction by introducing the concept of four areas focusing craftsmanship, the corresponding intellectual process, the filter-effects and the impact on participants’ communication.